Evaluation of In Vivo Antidiabetic, In Vitro α-Amylase Inhibitory, and In Vitro Antioxidant Activity of Leaves Crude Extract and Solvent Fractions of Fresen (Melianthaceae) - Zemene Demelash Kifle; Engidaw Fentahun Enyew (SAGE Publishing, 2020)
Background. The leaves of Bersama abyssinica are used for the treatment of diabetes mellitus in folk medicine system of Ethiopia. The present study was done based on the traditional claim of B abyssinica for the treatment of diabetes mellitus. Methods. The α-amylase inhibition and antioxidant activities of B abyssinica extracts were evaluated by using 3,5-dinitrosalicylic acid method and diphenyl-2-picrylhydrazyl assay model, respectively. Blood glucose lowering activity of the extracts was studied in 4 animal models; normoglycemic, oral glucose loaded, and streptozotocin-induced diabetic mice models. Results. Among the extracts, the crude extract showed the highest α-amylase enzyme inhibition activity with an IC 50 of 6.57 μg/mL. The water fraction showed the strongest antioxidant activity with an IC 50 of 3.43 μg/mL. The crude extract at doses of 200, and 400 mg/kg showed significant ( P < .05) hypoglycemic activity in normoglycemic mice. All doses of the crude extract significantly ( P < .05) reduced blood glucose levels of oral glucose-loaded mice. In streptozotocin-induced diabetic mice models, both the crude and solvent fractions showed a significant ( P < .05) blood glucose lowering effect as compared with the negative control group post 8 hour treatment. Conclusion. The results demonstrated the beneficial biochemical effects of B abyssinica extract by inhibiting α-amylase and scavenging the free radicals. The crude extract and solvent fractions of B abyssinica had significant blood glucose lowering effect in all animal models.